Evaluation of different marking methods for spiny-cheek crayfish (Orconectes limosus) - Buřič M.; Kozák P.; Vích P. (Knowledge and Management of Aquatic Ecosystems, 2008)
Different methods of marking were evaluated for Orconectes limosus (CL = carapace length, 12–37 mm) under laboratory conditions: the use of passive integrated transponders, visible implant elastomers, visible implant alphanumeric tags, and cauterization. High survival (> 90%) was obtained with all methods tested. Tag retention and readability were evaluated immediately after marking, before and after ecdysis, with moult increments and number of moults been recorded. Marking using cauterization negatively affects the percent moult increment (PMI) of crayfish. The average PMI of 15 ± 0.88% did not differ between males (15 ± 1.41 mm) and females (15 ± 1.12 mm). It was found that PMI gradually decreased with an increase in CL. Sixty-one moults were observed, with 12 crayfish (6 juveniles and 6 adults) presenting two moults. Time between moults varied from 3 to 7 weeks. CL was increased with over 28 ± 2.68% due to two moults. Three females moulted twice after successful hatching and carrying of juveniles.